KEMAMPUAN GENERALISASI MATEMATIS MELALUI PENDEKATAN KETERAMPILAN METAKOGNITIF DI SMP NEGERI MEGANG SAKTI - As Elly S; Rani Refianti (LP4MK STKIP PGRI Lubuklinggau, 2022)
This study aims to examine the effect of the metacognitive skills approach in learning mathematics on the mathematical generalization ability of the students of SMP Negeri Megang Sakti. The type of research used is a quasi-experimental research. This research was conducted in class VII1 as the experimental class and class VII2 as the control class. The population in this study were all seventh grade students of SMP Negeri Megang Sakti. The experimental class uses a metacognitive approach and the control class uses conventional learning. The data collection method used is the technique test method. Data were analyzed using t-test. Based on the analysis of the final test, the average value of the experimental class was 80.06 and the control class was 67.24 with Sgab = 9.65, based on the calculations on the hypothesis test, the value of tcount = 5,323 > ttable = 1,669. So it can be concluded that there is an effect of the metacognitive skills approach in learning mathematics on the generalization ability of students at SMP Negeri Megang Sakti.